THEORETICAL AND METHODOLOGICAL BASIS OF DEVELOPMENT OF HYGIENE CULTURE IN STUDENTS (Scientific journal of the Fergana State University, 2023)
In this article emphasized the theoretical and methodological basis for the development of hygienic culture in students, the study of the impact of hygienic environmental factors on human health and the study and development of the external environment, the promotion of human health on the basis of the information obtained.